2014
DOI: 10.4049/jimmunol.1400628
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complexes Inhibit IL-1 Secretion and Inflammasome Activation

Abstract: Immunoglobulin G (IgG) immune complexes have been shown to modify immune responses driven by antigen presenting cells in either a pro- or anti-inflammatory direction depending upon the context of stimulation. However, the ability of immune complexes to modulate the inflammasome-dependent innate immune response is unknown. Here we show that IgG immune complexes suppress IL-1α and IL-1β secretion through inhibition of inflammasome activation. The mechanism by which this inhibition occurs is via immune complex li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
1
21
1
Order By: Relevance
“…Another recent study indicated that immune complexes inhibit inflammasome activation (90). However, in the study by Janczy et al (90), immune complexes interfered with inflammasome assembly induced by a separate priming signal.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another recent study indicated that immune complexes inhibit inflammasome activation (90). However, in the study by Janczy et al (90), immune complexes interfered with inflammasome assembly induced by a separate priming signal.…”
Section: Discussionmentioning
confidence: 91%
“…However, in the study by Janczy et al (90), immune complexes interfered with inflammasome assembly induced by a separate priming signal. In the current study, DENV alone or DENV immune complexes were the sole stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies have been proposed as host‐derived adjuvants before . Most of these studies have been with soluble immune complexes consisting of soluble antigen bound to a cognate antibody . This strategy targets the antigen to Fc receptor‐bearing antigen presenting cells, yet does not exploit a second feature of antibody‐mediated adjuvancy—the activation of complement.…”
Section: Discussionmentioning
confidence: 99%
“…Ig (IVIG) is a marketed product composed of Igs from thousands of human donors (1). While the mechanism by which IVIG restores functional humoral immunity in patients with antibody deficiencies are self-evident, the mechanisms by which IVIG regulates tolerance in patients with autoimmune disease are much more speculative (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The practical consequence of such mechanistic diversity and/or uncertainty has been the historic inability to develop a recombinant drug that is capable of recapitulating the antiinflammatory properties of IVIG.…”
Section: Introductionmentioning
confidence: 99%